Celiac Disease From Pathophysiology to Advanced Therapies - Kruzliak, Peter; Bhagat, Govind (IntechOpen, 2012)
Celiac disease (CD) is an immune-mediated enteropathy triggered by the ingestion of gluten-containing grains (including wheat, rye and barley) in genetically susceptible individuals. CD can manifest itself with a previously unappreciated range of clinical presentations, including the typical malabsorption syndrome and a spectrum of symptoms potentially affecting any organ system. Since CD often presents in an atypical or even silent manner, many cases remain undiagnosed and carry the risk of long-term complications, including anemia and other hematological complications, osteoporosis, neurological complications or cancer. The high prevalence of the disease and its variety of clinical outcomes raise several interesting questions. This book covers most of the aforementioned controversial and yet unresolved topics by including the contributions of experts in CD.What the reader will surely find stimulating about this book is not only its exhaustive coverage of our current knowledge of CD, but also provocative new concepts in disease pathogenesis and treatment.